First, rewrite the expression as:
#(44/-4)(x^3/x^4)(y^-4/y^5)(z^2/z^-8) =>#
#-11(x^3/x^4)(y^-4/y^5)(z^2/z^-8)#
Next, use this rule for exponents to simplify the #x# and #y# terms:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#-11(x^color(red)(3)/x^color(blue)(4))(y^color(red)(-4)/y^color(blue)(5))(z^2/z^-8) =>#
#-11(1/x^(color(blue)(4)-color(red)(3)))(1/y^(color(blue)(5)-color(red)(-4)))(z^2/z^-8) =>#
#-11(1/x^(color(blue)(4)-color(red)(3)))(1/y^(color(blue)(5)+color(red)(4)))(z^2/z^-8) =>#
#-11(1/x^1)(1/y^9)(z^2/z^-8) =>#
#-11/(x^1y^9)(z^2/z^-8)#
Then, use this rule for exponents to simplify the #z# term:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#-11/(x^1y^9)(z^color(red)(2)/z^color(blue)(-8)) =>#
#-11/(x^1y^9)(z^(color(red)(2)-color(blue)(-8))) =>#
#-11/(x^1y^9)(z^(color(red)(2)+color(blue)(8))) =>#
#-11/(x^1y^9)(z^10) =>#
#-(11z^10)/(x^1y^9)#
Now, use this rule for exponents to complete the simplification of the #x# term:
#a^color(red)(1) = a#
#-(11z^10)/(x^color(red)(1)y^9) => #
#-(11z^10)/(xy^9)#